The Drosophila kekkon genes: Novel members of both the leucine-rich repeat and immunoglobulin superfamilies expressed in the CNS. - Musacchio, M.; Perrimon, N. (Developmental Biology, 1996)
We have identified two members of a novel class of genes in Drosophila that encode putative transmembrane proteins with six leucine-rich repeats and a single immunoglobulin loop. These two molecules, Kek1 and Kek2, show striking conservation in their extracellular domains and have large and more divergent intracellular regions. Both genes are expressed in neurons as they differentiate in the embryonic central nervous system (CNS). kek1 is also expressed in other patterned epithelia, such as the follicle cells of the developing egg chamber, where it is found in a dorsal-ventral gradient around the oocyte. The homology of the kek genes to other known adhesion and signaling molecules, together with their expression patterns, suggests that both genes are involved in interactions at the cell surface. Genetic analysis reveals that deletion of the kek1 gene causes no obvious developmental defects. The coexpression of kek2 in the CNS leads us to suggest that Kek1 is part of a family of cell surface proteins with redundant function.